Strategi Penetapan Harga Berbasis Personal Branding Pada Platform Tiktok: Studi Netnografi - Apolonia Emriant Meo; Asti Irawati; Fadhilah Fadhilah; Nina Yusnita Yamin (Journal of Applied Accounting, 2026)
This study aims to analyze the pricing strategies implemented by influencers in the digital era, where selling prices often exceed the intrinsic value of the product through the use of personal branding. From a management accounting perspective, this phenomenon creates a disparity between production costs (cost-based) and value-based pricing. Using a qualitative approach with netnography methods, this study explores digital consumer interactions and culture. The research data comes from netizens' comments on promotional content for the products "Risol Cucuapho" and "Donat Pinkan Mambo" on the TikTok platform. The analysis reveals three main categorizations of consumer price perception: negative, positive, and neutral. Negative perceptions arise when consumers identify an imbalance between the price paid and the physical quality of the product (perceived quality). Conversely, positive perceptions are formed when consumers internalize the added value of prestige and emotional closeness with the influencer as compensation for the premium price. These findings confirm that from a management perspective, influencer product pricing strategies no longer rely on traditional cost structures, but rather rely heavily on the influencer's capabilities in managing the intangible asset of brand image. This study concludes that management accounting in the digital era needs to expand the scope of value analysis by considering the influence of psychological and social factors in determining the fairness of prices in virtual markets. Keywords: Pricing Strategy, Personal Branding, Netnography, Consumer Value